The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1371/journal.pone.0142609
|View full text |Cite
|
Sign up to set email alerts
|

Decrease in Sphingomyelin (d18:1/16:0) in Stem Villi and Phosphatidylcholine (16:0/20:4) in Terminal Villi of Human Term Placentas with Pathohistological Maternal Malperfusion

Abstract: Placental villi play pivotal roles in feto-maternal transportation and phospholipids constitute a major part of the villous membrane. We have been developing and optimizing an imaging system based on a matrix-assisted laser desorption/ionization (MALDI)-based mass spectrometer, which provides clear two-dimensional molecular distribution patterns using highly sensitive mass spectrometry from mixtures of ions generated on tissue surfaces. We recently applied this technology to normal human uncomplicated term pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 45 publications
0
16
0
2
Order By: Relevance
“…After weighing and checking the gross morphology, whole placentas were stored in our pathological division after being vacuum-sealed in plastic packages with 10% formaldehyde (0.1 M sodium citrate buffer, pH 7.4). Seven paraffin blocks were systematically obtained from each placenta for the pathological examination by systematic random sampling, as previously described [ 12 , 13 ]. In brief, linear parallel slices of placental tissue, 5mm width, were made approximately every 3cm interval perpendicular to the greatest dimension of placental axis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…After weighing and checking the gross morphology, whole placentas were stored in our pathological division after being vacuum-sealed in plastic packages with 10% formaldehyde (0.1 M sodium citrate buffer, pH 7.4). Seven paraffin blocks were systematically obtained from each placenta for the pathological examination by systematic random sampling, as previously described [ 12 , 13 ]. In brief, linear parallel slices of placental tissue, 5mm width, were made approximately every 3cm interval perpendicular to the greatest dimension of placental axis.…”
Section: Methodsmentioning
confidence: 99%
“…Because placental pathology represents not only pathophysiological changes, but also physiological placental adaptations to various environmental factors, such as infection, malcirculation, chronic hypoxia on the maternal and fetal sides, and maternal hyperglycemia [ 10 , 11 ]. We recently demonstrated that changes in specific lipid profiles in the villi were responsible for pathologically abnormal placental findings using a two-dimensional imaging system based on a matrix-assisted laser desorption/ionization (MALDI)-based mass spectrometer [ 12 ]. We also showed that assisted reproductive technology affected the morphology of the placental basal plate [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Alterations in the spatial distribution of these molecules have been correlated with disease. Specifically, the absence of PC(16:0/20:4) in the terminal villi and absence of SM(d18:1/16:0) in the stem villi have been linked to morphological changes in the placenta due to maternal underperfusion [26]. These observations have proven very exciting, but while MSI offers unique opportunities to study the in situ spatial distribution, it does suffer from lower sensitivity due to ionization suppression of highly concentrated species concealing low concentration molecules.…”
Section: Conventional Metabolomics Tools For Understanding Pregnanmentioning
confidence: 99%
“…Фосфоинозидная рецепторная система играет важную роль в регуляции действия половых стероидов, и снижение уров-ня этого фосфолипида будет нарушать реализацию гормональных эффектов. Что касается ФЭ, то, кроме общих функций поддержания структуры и свойств мембран, он влияет на скорость АТФазной реакции, участвуя тем самым в обеспечении энергетического баланса плаценты, который, несомненно, будет нарушаться при уменьшении содержания ФЭ [10].…”
Section: результаты и обсуждениеunclassified
“…В настоящее время данные о биохимическом составе плазматических мембран микроворсин синцитиотрофобласта, обеспечивающего основной обмен между организмами матери и плода, немногочисленны и касаются лишь отдельных компонентов [7][8][9][10]. Ранее неизвестные сведения о составе и свойствах мембран плаценты позволяют углубить современные представления о механизмах развития ПН.…”
unclassified